1996
DOI: 10.1093/brain/119.6.1809
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulospinal, reticulospinal and descending propriospinal nerve fibres in man

Abstract: The course and location of vestibulospinal, reticulospinal and descending propriospinal fibres in man are reported. The investigation was carried out on three patients with supraspinal lesions, four with transection of the spinal cord and 33 with anterolateral cordotomies. The lateral vestibulospinal tract at the medullospinal junction and in the first three cervical segments lies on the periphery of the spinal cord lateral to the anterior roots. It moves to the sulcomarginal angle in the remaining cervical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(141 citation statements)
references
References 0 publications
3
136
0
1
Order By: Relevance
“…Sensory pathways are dominantly located in the posterior and anterior parts of the spinal cord white matter, whereas motor pathways are dominantly located more laterally. 9,10 Our hypothesis was that atrophy in the antero-posterior parts would be well correlated to sensory deficits, whereas atrophy in the left-right parts would be better correlated to motor deficits (see Figure 1a). Our aim was to introduce robust, sensitive and specific parameters to evaluate the functional state of individuals with SCI.…”
Section: Introductionmentioning
confidence: 93%
“…Sensory pathways are dominantly located in the posterior and anterior parts of the spinal cord white matter, whereas motor pathways are dominantly located more laterally. 9,10 Our hypothesis was that atrophy in the antero-posterior parts would be well correlated to sensory deficits, whereas atrophy in the left-right parts would be better correlated to motor deficits (see Figure 1a). Our aim was to introduce robust, sensitive and specific parameters to evaluate the functional state of individuals with SCI.…”
Section: Introductionmentioning
confidence: 93%
“…The spinal networks responsible for the locomotion timing pattern are likely to be distributed across several spinal segments linked by long propriospinal connections [as suggested by Nathan et al (1996)] including both descending and sensory inputs (Kiehn et al, 1998;Orlovsky et al, 1999;Dietz, 2002). Some evidence for this may be seen in spinal cord injury patients with both complete and incomplete spinal transections (Ivanenko et al, 2003).…”
Section: Proposed Superposition Of Motor Programsmentioning
confidence: 99%
“…In the human, the major locus of CPG circuitry is in the lumbosacral enlargement and coupling of cervical and lumbosacral CPGs may depend on the strength of propriospinal connections. Indeed, cervical and lumbosacral enlargements in humans appear to be coupled by long propriospinal neurons projecting to different pools of alpha motor neurons across several spinal segments (Nathan et al 1996). Moreover, reflex studies have suggested that stimulation of upper limb nerves can influence lower limb muscle activation during rhythmic activity and vice versa (Haridas and Zehr 2003;Zehr et al 2004).…”
Section: :1 Limb Frequency Relationshipmentioning
confidence: 99%